Efeitos de diferentes agrotóxicos na sobrevivência e comportamento de Scaptotrigona aff. xanthotricha (Apidae, Meliponini) - Ferreira, Maria Fernanda de Oliveira (2019)
The stingless bees are included in the group of the main pollinators whose ecological service is extremely important. However, they are undergoing serious threats, which are causing a decline in their populations. Standardized tests with Apis melífera are already common, and there is a need to create adequate parameters for stingless bees. Among the factors identified as possible causes for its decline is pesticide poisoning. This work evaluated the lethal dosages, lethal time and sub-lethal effects (through behavioral tests) of two insecticides used in soybean crops: abamectin and acetamiprid in Scaptotrigona aff. xanthotricha Moure, 1950 (Apidae, Meliponini). Acetamiprid is a neonicotinoid considered extremely toxic and abamectin is a medically toxic avermectin. The objective was to evaluate these effects, confirm this premise and propose simple and applicable methodologies for behavioral tests. The DLs found for abamectin were LD50 = 0.6993 μg / mL and DL90 = 0.90837 μg / mL; and for acetamiprid, LD50 = 0.494 μg / mL and LD90 = 0.753 μg / mL. The TLs were, under the effect of abamectin, 8.25 hours and under the effect of acetamiprid were 14.25 hours. For the Proboscis Extension test there were significant differences between abamectin and control (z = 1.14, P <0 .0001), and between acetamiprid and control (z = 5.87, P <0.0001), but not between abamectin and acetamiprid. For the locomotor activity test there were significant differences in the duration of the walk, acetamipid contaminated bees took up to 413 seconds to complete the race, while the maximum time of the control group was only 91 seconds. These results suggest that acetamiprid reduces the dispersal capacity of bees. For abamectin, there was no significant difference. Our results corroborate the hypothesis that acetamiprid is more toxic to S. aff. xanthotricha, but abamectin was also detrimental (except for the locomotion test). Similar studies carried out with A. melífera show that they are less sensitive to insecticides when compared to stingless bees, but some studies indicate a greater sensitivity to abamectin. Behavior tests represent bees activities in their living habits, thus showing how they are affected and impaired by the cognitive alteration caused by insecticides. The organisms respond differently to insecticides, body size, metabolism, foraging habits, are factors that alter these responses. Depending on the dose, the insecticides can act increasing or decreasing the metabolism of the bees. The standardization of methodologies for stingless bees is extremely important, the analyzes have to fit the limits of this group of social bees. These researches are fundamental for the understanding of factors that cause this decline of the population, so that a correct management is made and for the preservation of the species is carried out, avoiding third damages to the ecosystem.